The open door of PInAC. International Art Gallery of the evolutionary age. Aldo Cibaldi. (Journal of Parents and Teachers, 2016)
It describes the PInAC’s mission, an unique museum institution in Italy and in Europe which have children’s paintings from the whole world and the tasks which it develops. There are exhibitions between the activities which shows chosen canvas by their esthetic and representative quality, it is able to lead the stereotypes, to tell the origin places, the reference cultures, the genre belonging, the reference age and each individual experience.
Keywords: Childish expression; artists and education; cultural miscegenation; education in the enjoyment of the museum patrimony; education for pace; teacher’s training.